Public Knowledge About Pulmonary Tuberculosis (Tb): a Cross-Sectional Study in Indonesia - Fitriani Kahar; Irnawati; Muh Yusuf; Ririh Jatmi; Abdul Salam; Abdul Wadood (MultiTech Publisher, 2023)
Tuberculosis or TB is a disease caused by the acid-fast bacillus Mycobacterium tuberculosis. Transmission of the disease through inhalation of air droplets infected with Mycobacterium tuberculosis bacteria. The aim of this research is to determine the description of public knowledge about TB disease in terms of concepts, facts and procedures. The research method used was descriptive research with a cross-sectional design to see a picture of public knowledge about TB disease. The research population was people from 3 villages, namely Tlogosari Kulon, Tlogosari Wetan and Bangetayu Wetan. The sample size was 176 people chosen randomly. Data collection techniques use questionnaires and interviews with respondents. The research results obtained showed that the majority of respondents' knowledge was in the high category, namely 160 frequency or 90.9%. Concept knowledge shows a high category, namely 162 frequencies or 92%. Knowledge Facts shows a high category, namely 152 frequencies or 86.4%. Procedural knowledge shows a high category, namely 127 frequencies or 72.2%. The conclusion shows that most of the public's knowledge is in the high category.